Analisis Tingkat Resapan Tanah Berdasarkan Pengukuran Permeabilitas Tanah pada Sub DAS Bendung Palembang - Putri, Amalia Dwi; Saleh, Edward; Siswanto, Ari (Cantilever: Jurnal Penelitian dan Kajian Bidang Teknik Sipil, 2025)
The varying characteristics of soil in the Bendung watershed influence water infiltration processes, and soil permeability is an important indicator for assessing the soil's effectiveness in absorbing water. The relationship between permeability and water absorption capacity can help determine the risk level of waterlogging and flooding in the Bendung watershed. The study aims to analyze soil permeability variations in the Bendung watershed and their impact on flooding events. The method used is the Falling Head Test to accurately measure soil permeability at 14 locations, by measuring water height in a pipe inserted into the soil. Permeability values vary, with the highest value of 12.129 cm/hour in locations with sandy soil, while locations with clay content have lower permeability values, at 0.756 cm/hour. There is a connection between soil permeability and waterlogging. Soils with low permeability tend to cause water accumulation, increasing flood risk due to saturated soil. Conversely, high permeability indicates good water absorption capacity, as sandy soils have pores that effectively allow water to pass through. Soils with high sand content have higher permeability values, aiding water absorption in waterlogged areas. Clay soils have lower permeability and tend to cause waterlogging, increasing flood risk due to their saturated properties.